Antibacterial activity of five selected fruit’s peels in Kuala Pilah / Nik Nurul Aini Che Isa - Che Isa, Nik Nurul Aini (2018)
A research was carried out on five selected fruit’s peels namely watermelon (Citrullus lanatus), honey dew (Cucumis melo l.), dragon fruit (Hylocereus polyrhizus), papaya (Carica papaya) and banana (Musa acuminata) that were obtained from agro market Kuala Pilah, Negeri Sembilan by determining the antibacterial activity against Escherichia coli and Salmonella species. Three methods were used in order to analyse the antibacterial activity from these plants extract which were disc diffusion, minimum inhibition concentration (MIC) and time kill study. Based on disc diffusion results, the highest and smallest inhibition zone recorded were 16±0.10 mm and 6±0.00 mm respectively. Two fruit’s peels extract for each bacteria that obtained the highest inhibition zone were chosen in order to proceed with MIC which were papaya and watermelon extracts for the test against Escherichia coli while papaya and banana extracts for the test against Salmonella. For MIC, the least concentration of extract that showed less turbidity was at 25 mg/mL of papaya extract against Salmonella. As for time kill study, the papaya extract actively killed the bacteria at 8 hours. The results obtained provide the evidence that the five selected fruit’s peels especially papaya can be exploited more on its antibacterial potential as a source of antibacterial drug to be used in medicinal field in future.